Open Pension Schemes – the Effect of Pension System Privatization (Economic and Political Thought, 2013)
Open Pension Schemes in Poland (OFE) result from the privatization ofthe pension system implemented in response to the World Bank demands.The privatization of this kind has been implemented only in a few countriesin the world, in Latin America, Asia and East-Central Europe. Practically, itturned out that the existence of an obligatory capital pillar became the mainsource of public debt and as a result a threat to the stability of public finance.In Poland, since 1999, half of the increase in public debt has been causedby OFE. The continuation of the obligatory capital pillar maintenance willresult in the necessity to raise taxes and reduce important public spending.Financing OFE by increasing public debt may become impossible becauseof the precautionary public debt thresholds specified in the Act on PublicFinance and the Constitution. Additional limitations result from the necessityto undertake action indispensable in order to make the Council of the EuropeanUnion lift the procedure of excessive deficit imposed on Poland in 2009.